PERAN DINAS PERTANIAN DAN PERIKANAN KOTA PEKANBARU TERHADAP PETANI SAYUR DI KELURAHAN MAHARATU KECAMATAN MARPOYAN DAMAI TAHUN 2021 - Tebi, Fitra Nurzulio Indra; ,, Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This thesis is motivated by the lack of attention, especially to the provision of facilities and infrastructure for vegetable farmers. There is a lack of outreach or outreach to vegetable farmers in Maharatu Village. The purpose of this thesis is to determine the role of the Pekanbaru City Agriculture and Fisheries Office on vegetable farmers in Maharatu Village and to determine the influence of the Pekanbaru City Agriculture and Fisheries Office on vegetable farmer empowerment in Maharatu Village. The researcher used a qualitative research approach. The research location was agricultural land in Maharatu Village, Marpoyan Damai District, and the Pekanbaru City Agriculture and Fisheries Office. The types and sources of data in this study were primary data in the form of interviews and observations conducted by the researcher, while secondary data supported the primary data, namely the Pekanbaru City Profile, the Pekanbaru City Police Profile, and information about the Tanjak Polresta Application. Data collection techniques used were interviews and documentation. Meanwhile, data analysis was carried out using qualitative analysis. Based on the research results and discussion, it can be concluded that the role of the Pekanbaru City Agriculture and Fisheries Office in empowering vegetable farmers in Maharatu Village, Marpoyan Damai District in 2021 is evident in the implementation of facilitator indicators, which provide assistance to vegetable farmers. Catalyst indicators include providing high-quality seeds at affordable prices. Regulatory indicators, however, are not implemented due to the lack of training programs for vegetable farmers, and dynamic indicators include the limited number of visits by the Pekanbaru City Agriculture and Fisheries Office to vegetable farmers. The influence of the Pekanbaru City Agriculture and Fisheries Office on empowering vegetable farmers in Maharatu Village includes conducting training, providing counseling, and providing seed and fertilizer assistance. Keywords: Role, Pekanbaru City Agriculture and Fisheries Office, and Vegetable Farmers